Testing Two Trichoderma Biofertilizer Formulas on Soybean Plants Using Saline Soil as a Growing Medium - Amin Rahmatullah; S Sutarman (Demeter: Journal of Farming and Agriculture, 2025)
This study aims to examine the effect of Trichoderma biofertilizer formulated with husks or biochar applied to the soil as fertilizer and biofertilizer sprayed on the canopy surface on the vegetative growth of soybean plants in saline soil. The study was designed as a factorial design with a randomized block design (RBD). The first factor was the application of biofertilizer as soil fertilization, consisting of: no biofertilizer (NPK fertilization) and biofertilizer with husk and biochar as carriers. The second factor was the spraying of biofertilizer on the canopy, consisting of: no spraying and spraying. Data on height, stem diameter, number of leaves, and time of flower emergence were analyzed using 5% ANOVA followed by 5% BNJ test. There was a significant interaction effect on plant height, stem diameter, and number of leaves at 42 and 56 days after planting. The combination of Trichoderma biofertilizer with husk carrier and canopy spraying produced the highest plant response in terms of plant height (53.19±3.51 cm), stem diameter (0.53±0.02 cm), and number of leaves (9.50±0.65 leaves), as well as earlier flowering (37.50±0.33 days). The application of Trichoderma biofertilizer formulated with rice husk as a carrier has the potential to be used in fertilizing soybean plants grown in saline soil.